Air quality in enclosed railway stations: Quantifying the impact of diesel trains through deployment of multi-site measurement and random forest modelling. (July 2020) - Font, Anna; Tremper, Anja H.; Lin, Chun; Priestman, Max; Marsh, Daniel; Woods, Michael; Heal, Mathew R.; Green, David C.
Abstract: Concentrations of the air pollutants (NO2 and particulate matter) were measured for several months and at multiple locations inside and outside two enclosed railway stations in the United Kingdom – Edinburgh Waverly (EDB) and London King's Cross (KGX) – which, respectively, had at the time 59% and 18% of their train services powered by diesel engines. Average concentrations of NO2 were above the 40 μg m −3 annual limit value outside the stations and were further elevated inside, especially at EDB. Concentrations of PM2.5 inside the stations were 30–40% higher at EDB than outside and up to 20% higher at KGX. Concentrations of both NO2 and PM2.5 were highest closer to the platforms, especially those with a higher frequency of diesel services. A random-forest regression model was used to quantify the impact of numbers of different types of diesel trains on measured concentrations allowing prediction of the impact of individual diesel-powered rolling stock. Graphical abstract: Image 1 Highlights: NO2 and PM concentrations greater inside stations compared to the urban air. NO2 in two enclosed railway stations in the UK above the EU Limit Value. Diesel services influenced both NO2 and PM2.5 concentrations inside stations. The rolling stock influencing station concentrations were identified. Abstract : Diesel emissions in two UK enclosed railway stations.